Gray glass having low light transmittance

A cost-effective gray glass composition for automotive applications, using iron, cobalt, selenium, and titanium oxides, addresses the high cost issue of rare earth oxides by achieving low light and solar transmittance, enhancing solar control and privacy.

JP2025010121APending Publication Date: 2025-01-20VITRO FLAT GLASS LLC
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
JP2024108718
Authority / Receiving Office
JP · JP
Patent Type
Applications
Current Assignee / Owner
Priority Date
2023-07-06
Filing Date
2024-07-05
Publication Date
2025-01-20

AI Technical Summary

Technical Problem

Existing gray glass compositions for automotive applications, such as panoramic roofs and rear doors, are costly due to the use of rare earth oxides and suffer from high optical properties, necessitating a more economical and effective solution.

Method used

A low light transmittance gray glass composition using iron oxide, cobalt oxide, selenium, copper oxide, and titanium oxide, with controlled redox conditions, is developed to achieve desired solar control properties without rare earth oxides, manufactured via a conventional float non-vacuum glass process.

Benefits of technology

The new glass composition achieves low visible light, direct solar, and UV transmittance, with infrared transmittance of 14% or less, and total solar transmittance below 50%, providing effective solar radiation control and privacy while reducing production costs.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure 2025010121000001
    Figure 2025010121000001
  • Figure 2025010121000002
    Figure 2025010121000002
  • Figure 2025010121000003
    Figure 2025010121000003
Patent Text Reader

Abstract

To provide a low light transmittance gray glass formed from a composition.SOLUTION: A low light transmittance gray glass formed from a composition includes colorants. The colorants include 1.8 wt.% to 2.3 wt.% of Fe2O3, 0.28 wt.% to 1.2 wt.% of FeO, 0.030 wt.% to 0.040 wt.% of Co3O4, 0.0020 wt.% to 0.010 wt.% of Se, 0.00050 wt.% to 0.050 wt.% of CuO, and 0.01 wt.% to 1 wt.% of TiO2. The glass has a visible light transmittance (TLA) of less than 15%, a direct solar transmittance (TDS) of less than 14%, an infrared transmittance (TIR) of less than 14%, an ultraviolet transmittance (TUV) of less than 8%, and a total solar transmittance (TTS) of less than 38%.SELECTED DRAWING: None
Need to check novelty before this filing date? Find Prior Art

Description

[Technical field]

[0001] background This application relates generally to a neutral gray colored low transmittance glass, and more specifically to a gray glass composition for use in the automotive industry, such as panoramic roofs and rear door side windows. [Background technology]

[0002] Technical considerations Tinted glass is a material in which metal oxides are incorporated during the process of melting. It is common to add iron-cobalt oxide in combination with selenium to obtain glass tints ranging from greenish gray or neutral gray to yellowish gray, depending on the ratio of additives. By controlling the concentrations of iron oxide, cobalt oxide, and selenium, and controlling the redox conditions in the glass melting atmosphere and / or mixture (mainly carbon and sodium nitrate concentrations), a glass can be obtained with low light transmission, desired blocking of direct solar radiation transmission, and gray tinting for privacy, which can be used in automotive applications for panoramic roofs and rear doors of vehicles. Disadvantages of currently used glass compositions include the high cost of using rare earth oxides required to obtain the desired material and optical properties.

[0003] Therefore, those skilled in the art continue to conduct research and development in the field of grey glass for use in the automotive industry. Summary of the Invention

[0004] Low light transmission gray glass formed from the composition is disclosed.

[0005] In one example, the low light transmittance gray glass has a composition that includes a colorant, which includes (by weight of the total glass) 1.8% to 2.3% Fe2O3, 0.28% to 1.2% FeO, 0.030% to 0.040% Co3O4, 0.0020% to 0.010% Se, 0.00050% to 0.050% CuO, 0.01% to 1% TiO2, and 15 to 40% Redox. The glass has a visible light transmittance (T) of 15% or less. LA ), direct solar transmittance (T DS ), infrared transmittance (T IR ), UV transmittance below 8% (T UV ), and a total solar transmittance (T TS ).

[0006] In one example, a low light transmittance gray glass is formed from a composition including 68% to 75% by weight SiO2, 0% to 5% by weight Al2O3, 5% to 15% by weight CaO, 0% to 10% by weight MgO, 10% to 18% by weight Na2O, 0% to 5% by weight K2O, and 0.05% to 0.3% by weight SO3, and a colorant including 1.8% to 2.3% by weight Fe2O3, 0.28% to 1.2% by weight FeO, 0.030% to 0.040% by weight Co3O4, 0.0020% to 0.010% by weight Se, 0.00050% to 0.050% by weight CuO, 0.01% to 1% by weight TiO2, and 15 to 40% redox. In another example, the glass should have a visible light transmittance (T LA ), direct solar transmittance (T DS ), infrared transmittance (T IR ), UV transmittance below 8% (T UV ), and a total solar transmittance (T TS ).

[0007] Also disclosed is a method for producing low light transmission grey glass using conventional float non-vacuum glass processes.

[0008] In one example, the method includes melting a glass batch to provide a pool of molten glass, flowing the pool of molten glass onto a molten tin bath, controllably cooling the molten glass and moving the molten glass over a surface of the molten tin bath while applying a force to the molten glass to provide glass of a desired thickness, and removing the glass from the molten tin bath, the glass being comprised of 68% to 75% by weight SiO2, 0% to 5% by weight Al2O3, 5% to 15% by weight CaO, 0% to 10% by weight MnO2, and / or 0% to 10% by weight ZnO. % to 0.5% by weight of SiO2, 10% to 18% by weight of Na2O, 0% to 5% by weight of K2O, and 0.05% to 0.3% by weight of SO3, and colorants including 1.8% to 2.3% by weight of Fe2O3, 0.28% to 1.2% by weight of FeO, 0.030% to 0.040% by weight of Co3O4, 0.0020% to 0.010% by weight of Se, 0.00050% to 0.050% by weight of CuO, 0.01% to 1% by weight of TiO2, and 15 to 40% by weight of redox. In one example, the glass has a visible light transmittance (T LA ), direct solar transmittance (T DS ), infrared transmittance (T IR ), UV transmittance below 8% (T UV ), and a total solar transmittance (T TS ).

[0009] Other examples will become apparent from the following detailed description, the accompanying drawings, and the appended claims. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS

[0010] As used herein, all numbers used in the specification and claims expressing dimensions, physical properties, processing parameters, amounts of ingredients, reaction conditions, and the like, should be understood to be modified in all instances by the term "approximately" or "about." Thus, unless indicated to the contrary, the numerical values ​​set forth in the following specification and claims may vary depending on the desired properties sought to be obtained by the present disclosure. At the very least, and without attempting to limit the application of the doctrine of equivalents to the scope of the claims, each numerical value should be interpreted at least in light of the number of reported significant digits and by applying ordinary rounding techniques. Furthermore, all ranges disclosed herein should be understood to encompass the beginning and ending values ​​of the range, and any and all subranges encompassed within that range. For example, a range described as "1 to 10" should be considered to include any and all subranges between (including) a minimum value of 1 and a maximum value of 10, i.e., any and all subranges beginning with a minimum value of 1 or more and ending with a maximum value of 10 or less, e.g., 1 to 3.3, 4.7 to 7.5, 5.5 to 10, etc. "A" or "an" refers to one or more.

[0011] As used herein, the phrase "at least one of," when used in conjunction with a list of items, means that one or more of the listed items may be used in various combinations and that only one of each listed item may be required. For example, "at least one of item A, item B, and item C" may include, but is not limited to, item A, or item A and item B. This example may also include item A, item B, and item C, or item B and item C. In other examples, "at least one of" may be, for example, but is not limited to, 2 item A, 1 item B, and 10 item C, or 4 item B and 7 item C, or other suitable combinations.

[0012] The present disclosure relates to compositions and methods for producing tinted glass. Tinted glass is a material in which metal oxides are incorporated during the process of melting. As a result of previous research, it is known that the addition of iron-cobalt oxide in combination with selenium can result in glass tints ranging from greenish gray or neutral gray to yellowish gray, depending on their ratio. By controlling the concentrations of iron oxide, cobalt oxide, and selenium, and controlling the redox conditions (mainly carbon and sodium nitrate concentrations) in the glass melting atmosphere and / or mixture, a glass can be obtained with low light transmission, desired blocking of direct solar radiation transmission, and gray tinting for privacy, which can be used in automotive applications for panoramic roofs and rear doors of vehicles.

[0013] The glass described in the examples below refers to a type of neutral grey glass based on three main colouring agents, namely iron oxide, cobalt oxide and selenium, whose main function is to give the glass solar control properties.

[0014] The following patents and publications provide examples of utilizing various metal oxides as the primary coloring agents to obtain gray glass and also provide the final properties of the product: These components, such as nickel oxide, manganese oxide, chromium oxide, or rare earth oxides, are mixed into a base formulation of silicon-soda-calcium glass.

[0015] For example, US Patent No. 5,352,640 to Combes et al. (US Reissue Patent No. RE37,998(E)) discloses obtaining a grey glass used primarily in the automotive industry, the composition of the colouring agent being in the range of 1.4-4% total iron and 0-0.05% cobalt oxide, with iron oxide in excess but cobalt at about 0.02% with less than 2% Fe2O3, and possibly with a combination of CoO+Se+Cr2O3 at a content of less than 0.24% by weight. The physical properties of the glass, such as light transmittance and energy transmittance, are less than 20% under Illuminant A and less than 12% at a thickness of 3.85 mm, respectively.

[0016] U.S. Patent No. 5,545,596 to Alvarez Casariego et al. discloses the use of dyes having concentrations of 0.45-2.5% total iron, 0.001-0.02% CoO, 0-0.0025% Se, and 0-0.1% Cr2O3 for gray glass used in vehicle side and rear windows and having a light transmittance of 20-60% under Illuminant A.

[0017] U.S. Patent No. 7,393,802 (B2) to Seto et al. discloses the use of Fe2O3, CoO, Se, and NiO as colorants, but also adds the use of CeO2 and TiO2 in amounts up to 2.0 wt % to increase the absorption of ultraviolet light.

[0018] In the glasses obtained in U.S. Patent No. 7,622,410, assigned to Longobardo et al., in addition to a total content of 0.15-0.45% iron oxide, not more than 3 ppm selenium, and 120-240 ppm cobalt oxide, nickel oxide in a concentration of 500-1000 ppm, erbium oxide (Er2O3) in a concentration of 0.1-0.8%, and chromium oxide in a content of 1-20 ppm are used. A mixture of these oxides is used to adjust the overall gray coloration of the glass. The glasses of this patent have a light transmittance of 8-25%, a dominant wavelength of 435-570 nm, a cobalt oxide / nickel oxide ratio of 0.22-0.30, and a redox value of FeO / Fe2O3 of 0.20-0.40. A significant drawback of these disclosed glasses is the high cost of using rare earth oxides required for the composition of these glasses.

[0019] In US Patent No. 8,017,538 (B2) to Teyssedre et al., the glass presented uses nickel oxide in concentrations of 400-700 ppm or 1500-1900 ppm, and 0.7-0.95% iron oxide with a redox value of 0.40 or less, in addition to 200-300 ppm of cobalt oxide, to obtain a gray color adjustment, and to obtain the following physical properties: a light transmission (TLA) of 50% or less and an average energy transmission (TE) of less than 45% under Illuminant A for a glass thickness of 3.85 mm. The use of nickel oxide, used as a colorant in some of the previous patents, has the drawback that nickel sulfide inclusions can be formed (a defect that is not easily detectable), which can cause the glass pane to break due to the difference in the thermal expansion coefficient between this material and the rest of the glassy matrix. The glasses described in US Patent No. 8,551,899 by Kim et al. have a dark neutral gray-green coloration due to the dyes used, e.g., 1.4-2.5% Fe2O3, 0.02-0.04% CoO, 0.0001-0.004% Se, 0.005-0.5% MnO, and 0.05-1% CeO, and have a light transmission of less than 15% under Illuminant A. These glasses are used as privacy glass or panoramic roofs in automobiles, as well as in construction.

[0020] In U.S. Patent No. 7,754,632, Delmotte et al. use concentrations of up to 600 ppm MnO and less than 0.1% TiO2, in addition to other oxides such as 1.1-1.5% (total iron) Fe2O3, 150-200 ppm Co, 25-100 ppm Cr2O3, and 10-50 ppm Se, to achieve optical properties of less than 20% light transmission with Illuminant A for a thickness of 4 mm.

[0021] U.S. Patent No. 8,785,338 to Tsuzuki et al. describes a ferrous alloy having a content of 0.70-1.70 wt.% Fe2O3 (total iron), 0.15-0.45 wt.% FeO (ferrous oxide), 0-0.8 wt.% TiO2, 100-350 ppm CoO, 0-60 ppm Se, 100-700 ppm Cr2O3, and 3-150 ppm MnO, with a ferrous to ferric ion ratio (Fe 2+ / Fe 3+ The patent mentions a silico-sodium-lime glass composition having a TiO2 content of 0.20 to 0.80. The patent discloses that the glass has excellent ultraviolet and infrared absorption (thermal insulation) properties in addition to sufficient transparency, preferably by using TiO2 in the range of 0 to 0.5%.

[0022] No. 9,120,695, Lee et al., discloses the following glass composition: 1.4-2% Fe2O3 with an FeO content of 10-30% (based on total iron), 0.02-0.035% CoO, 0.0015-0.004% Se, and 0.005-0.5% MnO. Optical properties are reported as less than 15% light transmittance under Illuminant A and less than or equal to 2% UV transmittance.

[0023] The dark green glass disclosed in U.S. Patent No. 9,617,182 to Cho et al. (April 11, 2017) discloses 1.2-2% total Fe2O3 as a dye, 0.0220-0.04% CoO, 0.002-0.0035% Se, and 0.01-0.04% Cr2O3, where the weight ratio of (CoO+Cr2O3) to Se (=[CoO+Cr2O3] / Se) is 13-25, and the weight ratio of CoO to Cr2O3 (=CoO / Cr2O3) is 0.9-1.8. The glass has a visible light transmittance (T) of 15% or less, measured on a 4 mm thickness basis. LA ), direct solar radiation energy transmittance (T DS ), and less than 3% UV transmittance (T UV ) is shown.

[0024] US Patent No. 7,902,097(B2) by Cid-Aguilar et al. uses concentrations of 0-30 ppm Co3O4, 1-20 ppm Se, 20-200 ppm CuO, and 0.30-0.70% Fe2O3 to obtain a neutral gray glass with optical properties of greater than 65% light transmittance at Illuminant A, 60% or less total solar energy transmittance, less than 46% UV transmittance, and dominant wavelength of 490-600 nm. The patent discloses the addition of ingredients such as 0.01-0.07% carbon or 0.2-1.2% sodium nitrate to modify the redox state of the iron and copper oxides, as this addition, in combination with other dyes, can be used as an alternative to partially replace the addition of titanium oxide and cobalt oxide to obtain gray hues.

[0025] According to the above disclosure, iron is present in the glass (silico-sodic-calcic) in two different compound forms depending on the oxidation state of iron: Fe 2+ When iron exists as Fe, the compound formed is ferrous oxide (FeO). 3+ When present as Fe2O3, the compound formed is ferric oxide (Fe2O3). Each ion confers different properties. Namely, ferrous ions have a broad and strong absorption band centered at 1050 nm, resulting in a reduction in infrared radiation. Moreover, this absorption band extends into the visible region, reducing light transmittance and giving the glass a blue tint. On the other hand, ferric ions exhibit a strong absorption band located in the ultraviolet region, which prevents ferric ions from transmitting through the glass. Furthermore, ferric ions exhibit two other weak absorption bands in the visible region located at 420-440 nm, which may cause a slight reduction in light transmittance and yellowing of the glass. Generally, the amount of iron in glass, and its ferrous oxide, is expressed in the form of Fe2O3. It is common to express the amount of ferrous oxide or ferric oxide as a percentage of the total iron. The balance between ferrous oxide and ferric oxide directly affects the color and transmittance properties of the glass, and can be expressed as follows:

number

[0026] The ferric ions (Fe 3+ The greater the amount of ferrous ions (Fe ) the greater the absorption of ultraviolet light, the greater the light transmission, and the yellowish hue. 2+ As the content of ) increases, infrared absorption increases, but ultraviolet absorption decreases, and light transmission also decreases.

[0027] [ka]

[0028] [ka]

[0029] With respect to Fe2O3, variations in FeO concentration cause color changes in the glass. The hue shift can vary from yellow to green, blue to amber. The colors vary as follows (based on experimental results): yellow-low ferrous (12%)-high light transmittance (high ferric ions); yellow-green (16%); green-yellow (20%); green (standard value for green glass 25%); teal green (29%); greenish blue (35%); blue (50%); olive green (60%); champagne (65%); and amber-high ferrous (75%)-low light transmittance (low ferric ions).

[0030] It is beneficial to establish conditions in the mixing and melting atmosphere to control the balance between ferrous and ferric oxides required to obtain solar control glass. In one aspect, the concentrations of reducing agents such as carbon and oxidizing agents such as sodium sulfate and sodium nitrate can be selectively adjusted. As far as melting conditions are concerned, it can be beneficial to adjust the atmosphere to a higher or lower oxygen content depending on the thermal performance and the desired color of the glass.

[0031] Titanium dioxide is also well known to act as a colorant and can be used in combination with Fe2O3 to obtain further reduction in UV transmittance up to the point where the desired visibility transmission is achieved.

[0032] KM Yles in the article "Modern Automotive Glasses", Glass Technology, Vol. 37, February 1996, pp. 2-6, discloses that iron is the most important colorant in automotive glass because it is a low-cost, available component that absorbs undesirable ultraviolet radiation (ferric ions) and even large amounts of infrared radiation (ferrous ions).

[0033] Gordon F. Bresterm et al., in the article "The color of iron-containing glasses of varying composition", Journal of the Society of Glass Technology, New York, USA, April 1950, pp. 332-406, disclose color changes produced by systematically varying the composition of iron-containing silicate and non-silica glasses, evaluated in terms of visual color, spectral transmittance, and chromaticity.

[0034] Other articles disclosing the importance of the balance between ferrous and ferric oxides in glass include "The equilibrium between ferrous and ferric oxides in glasses" by NEDensem, Journal of the Society of Glass Technology, Glasgow, England, May 1937, pp. 374-389, and JC Hostetter and H.S. Roberts, "Note on the dissociation of Ferric Oxide dissolved in glass and its relation to the color of iron-bearing glasses," Journal of the American Ceramic Society, USA, September 1921, pp. 927-938. Many scientific books and articles have been published on the composition of colored glasses with ultraviolet and infrared absorbing properties.

[0035] C.R. Baumford describes the principles and applications of glass coloring methods in his book Color Generation and Control in Glass, Glass Science and Technology (Elsevier Science Publishing Co., Amsterdam, 1977). In this book, the authors consider that three factors govern the color of light transmitted by glass: the color of the incident light, the glass's interaction with the incident light, and the interaction of the transmitted light with the observer's eye. This procedure requires the spectral transmittance data of the glass along with the corresponding glass thickness and viewing angle.

[0036] Regarding titanium oxide (TiO) in silico-sodium-calcic (silico-sodic-calcic) glasses, the most stable form of titanium in the glass is tetravalent (Ti 4+ ). The trivalent form can impart coloration, but this effect is not seen in silico-sodic-calcic glasses. An article by Beals MD entitled "Effects of Titanium Dioxide on Glass", The Glass Industry, September 1963, pp. 495-531, describes the interest that titanium dioxide has been shown to have as an ingredient in glasses. The effects of using titanium dioxide include comments that TiO2 greatly increases the refractive index, increases the absorption of light in the ultraviolet range, and reduces viscosity and surface tension. From data on the use of titanium dioxide in enamels, it has been observed that TiO2 increases chemical durability and acts as a flux. In general, clear glasses containing titanium dioxide can be found in all common glass-forming systems (borates, silicates, and phosphates). The various glass-forming regions for titanium dioxide-containing systems are not lumped together, since the discussion is based on the characteristics of the use of titanium dioxide-containing glasses rather than on the composition of the glasses themselves. On the other hand, the addition of selenium to silicon-sodium-lime glasses can produce a pink coloration due to the presence of selenium atoms. Selenium is one of the most widely used physical whitening agents for glasses that contain traces of iron mixed into the raw materials as an undesirable impurity. This is because the coloration due to selenium neutralizes the ferrous and ferric ions present in the glass. The combination of iron oxide and selenium in silicon-soda-lime glasses results in a reddish-brown coloration and a decrease in light transmittance due to an absorption band located in the visible region from 490 to 500 nm (similar to that of selenium atoms). This absorption band extends into the ultraviolet region, which also results in a decrease in this type of transmittance in the glass. The color intensity and final properties of the glass are a function of the concentrations of iron oxide and selenium in the glass.

[0037] It is well known that copper has played an important role in the manufacture of glass, ceramics, and color pigments. For example, the coloring of Persian pottery has been recognized by the color tones it imparts. Of particular interest to potters are turquoise blues, especially Egyptian dark blue and Persian dark blue (Waldemar A. Weil, "Colored Glasses," Society of Glass Technology, UK, pp. 154-167, 1976).

[0038] Copper has been used in glass compositions not only in the silico-sodic-calcic type of glasses, but also in some other glasses, such as those containing borosilicates. The resulting color therefore depends on the base of the glass, its concentration, and its oxidation state.

[0039] In sodium-silicon-calcium glasses, copper in oxide form gives a greenish-tinted blue coloration, specifically a turquoise coloration, but in glass, copper can be in its monovalent state, which gives no color. The blue-green coloration is therefore determined not only by the amount of copper present, but also by the ionic balance between the cuprous and cupric states. The absorption maximum of copper oxide is in a wavelength range centered at 780 nm, with a second weak maximum peak at 450 nm, which disappears at high soda contents (about 40% by weight) (CR Bamford, Color Generation and Control in Glass, Glass Science and Technology, Elsevier Scientific Publishing Company, pp. 48-50, Amsterdam, 1977).

[0040] The incorporation of copper oxide (CuO) in combination with iron oxide, cobalt oxide, selenium, and titanium oxide is an alternative to obtain low light transmittance grey shades for use in the automotive industry or construction, where the glass has a low illuminating light transmittance A(T) of 15% or less when it has a nominal thickness of 3.85 mm. LA ), direct solar transmittance (T DS ), near infrared transmittance (T IR ), UV transmittance below 8% (T UV ), total solar energy transmittance (T TS ), with a purity of 50% or less, and a dominant wavelength of 480-590 nm. In industrial production, it has been confirmed that it is feasible to add CuO at concentrations of less than 120 ppm for a thickness of 4 mm and less than 100 ppm for a thickness of 6 mm.

[0041] Solar control is the ability to modify the amount of solar radiation transmitted or reflected in the spectral intervals ranging from near ultraviolet (UV; 300-380 nm), visible (VIS; 380-780 nm), and infrared (IR; 780-2500 nm). Solar control may be achieved by adding various absorbing colorants to the initial mixture. The resulting glass has the property of absorbing both infrared (IR) and ultraviolet (UV) solar radiation to reduce the passage of excess heat to the interior of the vehicle caused by radiation from the sun, and also to protect the interior from degradation due to ultraviolet radiation from the sun.

[0042] The glass can also be produced in various thicknesses, such as the glass used to produce laminated systems. If higher concentrations of CuO are present, a reduction process can occur during the forming process in the float chamber, due to the atmosphere of this process. This results in a reddish coloration on the glass surface, which can be observed by reflection. This effect is related to the residence time and forward speed of the glass batten, which means that at slower speeds it is necessary to reduce the CuO content in the glass or adjust the reduction conditions in the float chamber.

[0043] The present disclosure relates to a gray glass. In one aspect, the present disclosure relates to a gray glass having a low illumination light transmittance A(T) of 15% or less when manufactured by a float process and has a nominal thickness of 3.85 mm. LA ), direct solar transmittance (T DS ), near infrared transmittance (T IR ), UV transmittance below 8% (T UV ), total solar energy transmittance (T TS ), has a purity of 50% or less, and a dominant wavelength of 480 to 590 nm.

[0044] In another aspect, the present disclosure relates to the use of copper oxide as a partial replacement for cobalt oxide (Co3O4). The feasibility of adding copper oxide to float-produced flat glass has been demonstrated to levels approaching 120 ppm without the reducing effects of tin chamber conditions. Similarly, TiO2 may be included as an additional element with iron oxide to further reduce UV transmittance. In another aspect, the present disclosure relates to a method for obtaining a low light transmittance grey glass composition that includes an additional element, such as carbon or sodium nitrate, to modify the redox state of the iron oxide.

[0045] The glasses of the present disclosure avoid the use of costly coloring compounds such as nickel, chromium, manganese, or rare earth oxides, primarily erbium oxide (Er2O3).

[0046] The present disclosure further relates to grey glass compositions that can be implemented in both automotive and non-automotive applications, such as in the construction industry or other applications, which can be used as substrates to be coated with single or thin multi-layers applied by means of Mesoscopic Vacuum Deposition (MSVD), Chemical Vapor Deposition (CVD), or other techniques.

[0047] A typical composition of silicon-soda-calcium glass for the automotive industry formed by the float glass process is characterized by the following formulation, based on weight percentages based on the total weight of the glass: 68% to 75% SiO2, 0% to 5% Al2O3, 5% to 15% CaO, 0% to 10% MgO, 10% to 18% Na2O, 0% to 5% K2O, and 0.05% to 0.3% SO3 by weight.

[0048] The glass composition of the present disclosure is based on a silica-soda-calcium glass to which one or more of the colorants described below are added to obtain a gray color. In one example, the composition includes 1.8% to 2.3% by weight Fe2O3, preferably about 2.0% to about 2.2% by weight Fe2O3, or more preferably 2.04 to 2.12% by weight Fe2O3, 0.28% to 1.2% by weight FeO, 15% to 40%, preferably 17% to 30%, more preferably 19% to 25% redox, 0.030% to 0.040% by weight Co3O4, 0.0020% to 0.010% by weight Se, 0.00050% to 0.050% by weight CuO, and 0.01% to 1% by weight TiO2. Additional agents that may be added to the composition to adjust redox include 0.01% to 1.0% NaNO3 by weight and 0% to 0.07% carbon by weight.

[0049] One benefit of adding sodium nitrate (NaNO3) and carbon to the composition is that it changes the oxidation state of the iron, thereby increasing the direct solar transmittance (T DS The objective of the present invention is to achieve an optimum level of visible light transmittance (T) of 15% or less when the glass has a thickness of, for example, 1.4-6 mm, 1.6-5 mm, or more preferably, 3.85 mm. LA ), direct solar transmittance (T DS ), infrared transmittance (T IR ), UV transmittance below 8% (T UV ), total solar transmittance (T TS), a purity of 50% or less, and a dominant wavelength of 480-590 nm. The glasses of the present disclosure avoid the use of coloring compounds such as nickel, chromium, manganese, or rare earth oxides, primarily erbium oxide (Er2O3).

[0050] The disclosure is further described in the following numbered sections:

[0051] Item 1. A low light transmittance gray glass formed from a composition including the following colorants: 1.8% by weight to 2.3% by weight of Fe2O3, 0.28% by weight to 1.2% by weight of FeO, 0.030% by weight to 0.040% by weight of Co3O4, 0.0020% by weight to 0.010% by weight of Se, 0.00050% by weight to 0.050% by weight of CuO, and 0.01% by weight to 1% by weight of TiO2, wherein the low light transmittance gray glass has a visible light transmittance (T LA ), direct solar transmittance (T DS ), infrared transmittance (T IR ), less than 8% UV transmittance (T UV ), and a total solar transmittance (T TS ) glass.

[0052] Item 2. The glass according to item 1, further having a redox ratio of 15 to 40%.

[0053] Item 3. The glass according to item 1 or 2, which has an excitation purity of 50% or less at a wavelength of 480 to 590 nm and a thickness of 3.85 mm.

[0054] Item 4. The glass according to any one of Items 1 to 3, wherein the glass composition further comprises 68% by weight to 75% by weight of SiO2, up to 5% by weight of Al2O3, 5% by weight to 15% by weight of CaO, up to 10% by weight of MgO, 10% by weight to 18% by weight of Na2O, up to 5% by weight of K2O, and 0.05% by weight to 0.3% by weight of SO3.

[0055] Item 5. The glass according to any one of Items 1 to 4, wherein the colorant further contains 0.01% by weight to 1.0% by weight of NaNO3.

[0056] Item 6. The glass according to any one of items 1 to 5, further comprising up to 0.07% by weight of carbon.

[0057] Item 7. A glass plate comprising the glass according to any one of items 1 to 6.

[0058] Section 8.D 65 Item 8. The glass plate according to item 7, which has the following color CIELAB values ​​when measured including a specular reflection component at an observer angle of 10° using an integrating sphere with a light source: an L* value in the range of 46 to 15, an a* value in the range of -10 to 5, and a b* value in the range of -5.0 to 15.

[0059] Item 9. The glass plate according to item 7 or 8, having a thickness of 3.85 mm and an excitation purity of 50% or less.

[0060] Item 10. The glass plate according to any one of Items 7 to 9, which has a dominant wavelength of 480 nm to 590 nm.

[0061] Item 11. The glass plate according to any one of Items 7 to 10, which is formed by a float process.

[0062] Item 12. A method for producing low light transmittance gray glass using a conventional float non-vacuum glass process, comprising melting a glass batch to provide a pool of molten glass, flowing the pool of molten glass onto a molten tin bath, controllably cooling the molten glass and moving the molten glass over a surface of the molten tin bath while applying a force to the molten glass to provide glass of a desired thickness, and removing the glass from the molten tin bath, wherein the glass comprises 1.8% to 2.3% by weight Fe2O3, 0.28% to 1.2% by weight FeO, 0.030% to 0.040% by weight Co3O4, 0.0020% to 0.010% by weight Se, 0.00050% to 0.050% by weight CuO, and 0.01% to 1% by weight TiO2, and the glass has a visible light transmittance (T) of less than 15%. LA ), direct solar transmittance (T DS ), infrared transmittance (TIR ), less than 8% UV transmittance (T UV ), and a total solar transmittance (T TS ).

[0063] Item 13. The method according to item 12, wherein the glass has a redox ratio of 15 to 40%.

[0064] Item 14. The method according to item 12 or 13, wherein the glass has an excitation purity of 50% or less at a thickness of 3.85 mm in a wavelength range of 480 to 590 nm.

[0065] Item 15. The method according to any one of items 12 to 14, wherein the glass further contains 68% by weight to 75% by weight of SiO2, 0% by weight to 5% by weight of Al2O3, 5% by weight to 15% by weight of CaO, 0% by weight to 10% by weight of MgO, 10% by weight to 18% by weight of Na2O, 0% by weight to 5% by weight of K2O, and 0.05% by weight to 0.3% by weight of SO3.

[0066] Item 16. The method according to any one of items 12 to 15, wherein the glass further contains 0.01% by weight to 1.0% by weight of NaNO3.

[0067] Item 17. The method according to any one of Items 12 to 16, wherein the dominant wavelength of the glass is 480 nm to 590 nm.

[0068] Item 18. A glass containing a colorant, the colorant including (based on the total weight of the glass) 1.8 wt. % to 2.3 wt. % Fe2O3, 0.28 wt. % to 1.2 wt. % FeO, 0.030 wt. % to 0.040 wt. % Co3O4, 0.0020 wt. % to 0.010 wt. % Se, 0.00050 wt. % to 0.050 wt. % CuO, 0.01 wt. % to 1 wt. % TiO2, and 15 to 40% redox.

[0069] Item 19. Visible light transmittance (T LA Item 19. The glass according to item 18, further comprising:

[0070] Item 20. Direct solar transmittance (T DS 20. The glass according to item 18 or 19, further comprising:

[0071] Item 21. Infrared transmittance (T IR 21. The glass according to any one of items 18 to 20, further comprising:

[0072] Item 22. Ultraviolet transmittance of 8% or less (T UV ), and a total solar transmittance (T TS 22. The glass according to any one of items 18 to 21, further comprising:

[0073] Item 23. The glass according to any one of items 18 to 22, further comprising 68% by weight to 75% by weight of SiO2, 0% by weight to 5% by weight of Al2O3, 5% by weight to 15% by weight of CaO, 0% by weight to 10% by weight of MgO, 10% by weight to 18% by weight of Na2O, 0% by weight to 5% by weight of K2O, and 0.05% by weight to 0.3% by weight of SO3.

[0074] Item 24. The glass according to any one of Items 18 to 23, wherein the amount of Fe2O3 is 2.0% by weight to 2.2% by weight.

[0075] Item 25. The glass according to any one of Items 18 to 23, wherein the amount of Fe2O3 is 2.04% by weight to 2.12% by weight.

[0076] example

[0077] The following example shows the light transmittance (T LA ), direct solar transmittance (T DS ), near-infrared transmittance (T IR ), UV transmittance (T UV ), total solar transmittance (T TS ) Color transmission (L*, a*, and b*), color purity, and dominant wavelength (l) for 3.85 glass.

[0078] Tables 1 and 2

[0079] Tables 1 and 2 (Examples 1-14) show experimental results of compositions of the present disclosure using combinations of iron oxide (Fe2O3), cobalt oxide (Co3O4), selenium (Se), copper oxide, and titanium oxide (TiO). Additionally, the compositions contain 0.66% sodium nitrate (NaNO3) as an oxidizer in the mixture without the addition of carbon.

[0080] [Table 1]

[0081] [Table 2]

[0082] [Table 3]

[0083] Table 3 (Examples 15-18) shows experimental results of compositions of the present disclosure using combinations of iron oxide (Fe2O3), cobalt oxide (Co3O4), selenium (Se), copper oxide, and titanium oxide (TiO). Additionally, 0.16% sodium nitrate (NaNO3) and 0.04% carbon (coke type) are incorporated into the mixture.

[0084] [Table 4]

[0085] [Table 5]

[0086] Tables 4 and 5 (Examples 19-31) show experimental results of compositions of the present disclosure using combinations of iron oxide (Fe2O3), cobalt oxide (Co3O4), selenium (Se), copper oxide, and titanium oxide (TiO). Similarly, the compositions contain 0.16% sodium nitrate (NaNO3) and 0.02% carbon in the mixture.

[0087] [Table 6]

[0088] Table 6 (Examples 32-34) shows experimental results of compositions of the present disclosure using combinations of iron oxide (Fe2O3), cobalt oxide or cobalt tetroxide (CoO or Co3O4), selenium (Se), copper oxide, and titanium oxide (TiO2). Additionally, the compositions contain 0.16% sodium nitrate (NaNO3) and 0.030% carbon. The primary purpose of adding sodium nitrate (NaNO3) and carbon to the compositions is to modify the oxidation state of iron to increase the direct solar transmittance (T DS The goal is to reach an optimal level of selenium. Additionally, sodium nitrate helps optimize the retention of selenium in the glass. Color and privacy are adjusted by optimizing the percentage of the dyes described in this disclosure.

[0089] Further examples of the present disclosure include the following shown in Table 7:

[0090] Table 7

[0091] Further experimental examples are shown in Table 8 below. [Table 7]

[0092] [Table 8-1] [Table 8-2]

[0093] The redox ratios of the above mentioned examples ranged from 0.2 to 0.3, with an average of 0.25. The physical properties of the resulting glasses were evaluated by internationally recognized standards. Specifications for the determination of color, such as dominant wavelength and excitation purity, were derived from the tristimulus colorimeter values ​​(x, y, and z) adopted by the International Commission on Illumination (CIE) as a standard and direct result of experiments involving many observers. These specifications can be determined by calculating the trichromatic coefficients x, y, and z of the tristimulus colorimeter values ​​corresponding to red, green, and blue, respectively. The trichromatic values ​​are plotted on a chromaticity diagram and compared with the coordinates of illuminant D65, which is considered to be the standard light. The comparison gives information for determining the color excitation purity and its dominant wavelength. The dominant wavelength specifies the wavelength of the color, and its value is within the visible range of 380 to 780 nm, while for excitation purity, the lower its value, the more neutral the color tends to be.

[0094] UV transmittance (T UV The calculation of UV transmittance is adjusted to the range of UV radiation from the sun. Therefore, UV transmittance was evaluated in the range 300-400 nm at 10 nm intervals, following the instructions in the ISO standard DIS 13837.

[0095] The light transmittance is evaluated using the light source "A" (T LA ) was used to integrate values ​​at 10 nm intervals over the wavelength range of 400-800 nanometers. Color transmission (L*, a*, and b*) was calculated according to ASTM E308 (CIED65 observer angle 10°).

[0096] Direct solar radiation transmittance (T DS ) values ​​were evaluated in the range of 300–2500 nm at intervals of 5, 10, and 50 nm according to the ISO / DIS 13837 standard.

[0097] Infrared transmittance (T IR ) using the values ​​of the ISO / DIS 13837 standard, a range having a range of 800 to 2500 nm (50 nm intervals), which is included in the radiation of the solar spectrum, is considered.

[0098] Total solar energy transmittance (T TS ) was evaluated in the range of 300–2500 nm, taking into account a wind speed of 4 m / s (stationary), according to the ISO / DIS 13837 standard.

[0099] The neutral grey glass of the present disclosure can be manufactured in thicknesses of 1.4 mm to 6 mm by the float glass process. However, the present disclosure is not limited to this thickness range and can be processed as a temper in glazing systems, double laminated systems, or as a substrate covered by one or more layers.

[0100] This glass has the following properties: light transmittance (T LA ), direct solar transmittance (T DS ), near infrared transmittance (T IR ), UV transmittance below 8% (T UV ), total solar energy transmittance (T TS ), and purity of 50% or less.

[0101] Those skilled in the art will readily appreciate that modifications may be made to the present disclosure without departing from the concepts disclosed in the foregoing description. Accordingly, the specific examples detailed herein are illustrative only and do not limit the scope of the present disclosure, which is to be accorded the full scope of the appended claims and any and all equivalents thereof.

Claims

1. Low light transmission grey glass formed with the following colourants: 2.04% to 2.12% by weight of Fe 2 O 3 , 0.28% to 1.2% by weight of FeO, 0.030% to 0.040% by weight Co 3 O 4 , 0.0020 wt.% to 0.010 wt.% Se, 0.00050% to 0.050% by weight of CuO, and 0.01% to 1% by weight of TiO 2 .

2. Visible light transmittance (T LA 2. The glass of claim 1 having a

3. Direct solar transmittance (T DS 2. The glass of claim 1 having a

4. Infrared transmittance (T IR 2. The glass of claim 1 having a

5. UV transmittance (T UV ), and a total solar transmittance (T TS 2. The glass of claim 1 having a

6. 10. The glass of claim 1 further having a redox ratio of 15 to 40%.

7. 10. The glass of claim 1 having an excitation purity of 50% or less at a thickness of 3.85 mm at wavelengths from 480 to 590 nm.

8. 68% to 75% by weight of SiO 2 , 0% to 5% by weight of Al 2 O 3 , 5% to 15% by weight of CaO, 0% to 10% by weight of MgO, 0% to 18% by weight of Na 2 O. 0% to 5% by weight of K 2 O, and 0.05% to 0.3% by weight of SO 3 10. The glass of claim 1 further comprising:

9. The colorant is 0.01% by weight to 1.0% by weight of NaNO 3 10. The glass of claim 1 further comprising:

10. 10. The glass of claim 1, wherein the colorant further comprises 0 to 0.07 weight percent carbon.

11. Fe 2 O 3 2. The glass of claim 1 , wherein the amount of is from 2.0% to 2.2% by weight.

12. Fe 2 O 3 2. The glass of claim 1 , wherein the amount of is from 2.04% to 2.12% by weight.

13. 2. The glass of claim 1, having the following color CIELAB values ​​when measured using an integrating sphere with a D65 light source at an observer angle of 10° and including a specular reflection component: L* value in the range of 46 to 15; an a* value in the range of −10 to 5, and b* values ​​ranging from -5.0 to 15.

14. A method for producing low light transmittance grey glass using a conventional float non-vacuum glass process, comprising: melting a glass batch to provide a pool of molten glass; casting the pool of molten glass onto a bath of molten tin; controllably cooling the molten glass and moving the molten glass over a surface of the molten tin bath while applying a force to the molten glass to provide a desired thickness of glass; removing the glass from the molten tin bath; Including, Glass colorants are 1.8% to 2.3% by weight of Fe 2 O 3 , 0.28% to 1.2% by weight of FeO, 0.030% to 0.040% by weight Co 3 O 4 , 0.0020 wt.% to 0.010 wt.% Se, 0.00050% to 0.050% by weight of CuO, and 0.01% to 1% by weight of TiO 2 A method comprising:

15. The method of claim 14, wherein the glass has a redox ratio of 15 to 40%.

16. The glass, 68% to 75% by weight of SiO 2 , 0% to 5% by weight of Al 2 O 3 , 5% to 15% by weight of CaO, 0% to 10% by weight of MgO, 0% to 18% by weight of Na 2 O. 0% to 5% by weight of K 2 O, and 0.05% to 0.3% by weight of SO 3 The method of claim 14 further comprising:

17. The glass contains 0.01% to 1.0% by weight of NaNO 3 The method of claim 14 further comprising:

18. The method of claim 14, wherein the dominant wavelength of the glass is between 480 nm and 590 nm.